Development of a digital numeracy assessment instrument based on Articulate Storyline for pre-service elementary teachers - Febry Rizki Susanti Kalaka; Dewi Darmiyani Napu; Indra A Otuhu (Journal Focus Action of Research Mathematic (Factor M), 2026)
Digital numeracy literacy is an essential competence for prospective elementary school teachers because it supports contextual problem-solving, data interpretation, and mathematical reasoning in 21st-century learning. However, contextual and technology-based assessment instruments capable of authentically measuring these competencies remain limited in teacher education. This study aimed to develop an interactive digital numeracy assessment instrument using Articulate Storyline, which supports multimedia-based and contextual assessment activities for prospective teachers in Madrasah Ibtidaiyah Teacher Education (PGMI) and Primary School Teacher Education (PGSD) programs. This research adopted a 4D Research and Development framework that included the stages of defining, designing, developing, and disseminating the instrument. The instrument was developed through needs analysis, expert validation, pilot, and field testing involving prospective teachers from three universities. The instrument contained contextual numeracy tasks of varying difficulty, covering geometry, measurement, equations, functions, ratios, and data representation. It was based on three digital numeracy indicators: mathematical symbol use, information analysis, and interpretation for decision-making. Validity was assessed through expert judgment, practicality through lecturer and student questionnaires, and effectiveness through variations in competencies across indicators and institutions. The findings indicated that the developed instrument achieved high validity and practicality and effectively identified variations in digital numeracy competencies across educational contexts. These findings indicate that the instrument can function as both an evaluation and diagnostic tool to support contextual and technology-based numeracy learning in teacher education.